PENGARUH PENGGUNAAN METODE PEMBELAJARAN PROBLEM BASED INSTRUCTION (PBI) DAN GUIDED INQUIRY (GI) TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA - noviani, fitri istria; Disman, D.; Rasto, R. (Program Studi Pendidikan Manajemen Perkantoran, 2018)
Education as a human process gains knowledge is vital in shaping the ability to think. Teachers, students, and teaching materials are the dominant elements in the learning process. The quality of teaching affects the effectiveness of the learning process and will impact on critical thinking skills. Learning is said to be effective when students are actively involved in organizing and finding information (knowledge) as well as linkage of information provided. Students not only passively receive the knowledge given by the teacher. Learning outcomes not only improve students 'understanding and absorption but also improve students' thinking skills. Thus in the learning needs to be considered how the involvement of students in organizing lessons and knowledge. The more active students in learning, the completeness of learning completeness is greater, so the more effectivelah learning Problem Based Instruction (PBI) and Guided Inquiry is one of the predicted learning model can improve students' critical thinking ability. Critical thinking skills are thinking of reasoning and reflective skills by pressing making decisions about what to believe and do.